Phase separation in the nonequilibrium Verwey transition in magnetite - Randi, Francesco; Vergara, I.; Novelli, Fabio; Esposito, Martina; Dell'Angela, Martina; Brabers, V. A. M.; Metcalf, P.; Kukreja, R.; Duerr, H. A.; Grueninger, M.; Parmigiani, F.; Fausti, Daniele (Physical Review B, 2016)
We present equilibrium and out-of-equilibrium studies of the Verwey transition in magnetite. In the equilibrium optical conductivity, we find a steplike change at the phase transition for photon energies below about 2 eV. The possibility of triggering a nonequilibrium transient metallic state in insulating magnetite by photo excitation was recently demonstrated by an x-ray study. Here we report a full characterization of the optical properties in the visible frequency range across the nonequilibrium phase transition. Our analysis of the spectral features is based on a detailed description of the equilibrium properties. The out-of-equilibrium optical data bear the initial electronic response associated to localized photoexcitation, the occurrence of phase separation, and the transition to a transient metallic phase for excitation density larger than a critical value. This allows us to identify the electronic nature of the transient state, to unveil the phase transition dynamics, and to study the consequences of phase separation on the reflectivity, suggesting a spectroscopic feature that may be generally linked to out-of-equilibrium phase separation.
CRIS-Team Scopus Importer:2022-07-20